Negotiating Gender Equality: NU Scholars’ Perceptions of Women’s Role in Sumenep - Rozi, Achmad Bahrur; Jamila, Lailatul; Nisa', Khairun; Rosmini, Rosmini; Ulfah, Ulfah (Islamica: Jurnal Studi Keislaman, 2025)
The 1997 National Conference of Nahdlatul Ulama (NU) Scholars in Lombok issued a groundbreaking fatwā permitting women to hold the position of vice president—a progressive step in advancing gender justice within Islamic discourse. However, at the grassroots level, gender segregation remains deeply entrenched, particularly in Sumenep Regency. This study explores how NU feminists in Sumenep negotiate their struggle for gender equality and how local kiai and religious scholars respond to these efforts. Employing a qualitative approach with data collected through literature review, observation, interviews, and documentation, this research is framed by Islamic feminist theory. The findings reveal that gender discourse in NU Sumenep remains weak when confronted with the religious authority of kiai and traditional scholars. Their ambivalent and skeptical responses toward gender equality activism indicate that the discourse promoted by the NU Central Board (PBNU) has not been effectively internalized at the local level. Furthermore, the absence of pesantren-based initiatives on gender awareness perpetuates gender segregation, resulting in unequal competencies and opportunities between male and female students. This study highlights the gap between NU’s progressive theological discourse and its limited cultural translation among rural communities.